If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(m/6)-4=-3
We move all terms to the left:
(m/6)-4-(-3)=0
We add all the numbers together, and all the variables
(+m/6)-4-(-3)=0
We add all the numbers together, and all the variables
(+m/6)-1=0
We get rid of parentheses
m/6-1=0
We multiply all the terms by the denominator
m-1*6=0
We add all the numbers together, and all the variables
m-6=0
We move all terms containing m to the left, all other terms to the right
m=6
| C=15n+450 | | (8x+14)+(12x-50)=80 | | 7x−30=19 | | 3x+12.2=18.5 | | 10-5v=20 | | x^2=3x*4 | | 3x+12.2=18.6 | | C(x)=20x+50 | | 7x+1+10x-32=90 | | x^2=x(x) | | (9x+5)=(12x-19)° | | 10+y/4=18 | | 196=-16t^2+196(0) | | 7(3w+5)/4=6 | | 7x+1+10x-32=180 | | 5(x*17)=$1,495 | | 12c-11=49 | | 98=x10 | | -8f=7-9f | | 52+2x=x+40 | | 3x+9-5=27 | | -n-2=-9n-10 | | 0y=0X+0 | | √(5-x)-1=x | | h/2-6=5 | | 28=-16+5x | | 7x=x*3 | | -14=-2+-3u | | 3w+2=-4-2w+1 | | 28=-26+5x | | F(-2)=4x-2+10 | | 1.2=0.75+r |